2015
DOI: 10.1007/s40279-015-0415-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Modulating Post-Activation Potentiation of Jump, Sprint, Throw, and Upper-Body Ballistic Performances: A Systematic Review with Meta-Analysis

Abstract: Performing a CA elicits small PAP effects for jump, throw, and upper-body ballistic performance activities, and a moderate effect for sprint performance activity. The level of potentiation is dependent on the individual's level of strength and resistance training experience, the type of CA, the depth of the squat when this exercise is employed to elicit PAP, the rest period between the CA and subsequent performance, the number of set(s) of the CA, and the type of load used during the CA. Finally, some componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
567
9
33

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(690 citation statements)
references
References 35 publications
17
567
9
33
Order By: Relevance
“…Research into PAP following the back squat exercise as a CA reports intensities exceeding 60% of 1 repetition maximum as optimal 18 , however a transferable value to sled towing is yet to be derived. It should be noted however, as indicated by Seitz & Haff 17 , how stronger effects are evident for repetition maximal loads (ES = 0.51) in comparison to sub-maximal loads (ES = 0.34), indicating how heavier sled loads hypothetically should be more optimal in eliciting a PAP effect. The findings from both the present study and those of Winwood et al 12 corroborate with this, with optimal sled loads identified at between 50-75% BM.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Research into PAP following the back squat exercise as a CA reports intensities exceeding 60% of 1 repetition maximum as optimal 18 , however a transferable value to sled towing is yet to be derived. It should be noted however, as indicated by Seitz & Haff 17 , how stronger effects are evident for repetition maximal loads (ES = 0.51) in comparison to sub-maximal loads (ES = 0.34), indicating how heavier sled loads hypothetically should be more optimal in eliciting a PAP effect. The findings from both the present study and those of Winwood et al 12 corroborate with this, with optimal sled loads identified at between 50-75% BM.…”
Section: Discussionmentioning
confidence: 89%
“…Further to this, a review by Petrakos, Morin, and Egan 7 examining longitudinal training implications indicates how sled towing with "light" loads (< 10% BM) may infact lead to decrements in sprint acceleration performance (-1.5%, ES = 0.50). On the contrary, "moderate to very heavy" loads (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).9% BM to > 30% BM) appear superior in lending itself to improvements in sprint acceleration performance (0.5-9.1%, ES = 0.14-4.00). This data is somewhat not surprising, given how recent findings by Cross et al…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the effect of resistance for a strong athlete would differ from that for a weaker athlete. Seitz and Haff [33] suggested that stronger athletes were able to exhibit a greater PAP effect than their weaker counterparts, since they may have a greater percentage of type II muscle fibres and therefore a greater phosphorylation of the myosin light chain [34]. In addition, stronger athletes may have developed fatigue resistance to heavier loads after a near-maximal effort, which might affect the balance between potentiation and fatigue after the conditioning stimulus [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is known as postactivation potentiation (PAP) and its use within the field of strength and conditioning has grown rapidly as performance enhancing effects have been demonstrated within athletic movements such as jumping (29,32) and sprinting (28). There are several suggested mechanisms behind PAP, including the recruitment of higher order motor units, increase in pennation angle, and the phosphorylation of myosin regulatory light chains (32).…”
Section: Introductionmentioning
confidence: 99%